Political analysis of the peace process in Colombia: a simulation from artificial neural networks - Toledo Ballén, Alfonso (Visión electrónica, 2014)
This article presents an exercise in political science simulation applied via artificial neural networks software called Easy NN-plus 15.0, with reference to possible political scenarios that can emerge once conclude the dialogue between the guerrillas of the armed revolutionary forces of Colombia (FARC-EP) and Juan Manuel Santos’s administration, whose aims to solve through negotiated via the internal armed conflict that is afflicting Colombia more than half a century ago. The political scenarios referred to as input layer for the Perceptron were: democratic stability, civil war, coup d’État, revolution, political reform and authoritarian modernization; the output layers were: democratic openness and the continuation of the conflict; while the interlayer was formed with the complex interrelationship of the six entry scenarios. The computer program was used to relate complex non-linear factors of the political challenge posed by the dialogue, to improve the analytical understanding of the situation.